The Effects of Establishing Intimacy and Consubstantiality on Group Discussions About Climate Change Solutions. Issue 3 (June 2020) - Bloomfield, Emma Frances; Van Swol, Lyn M.; Chang, Chen-Ting; Willes, Stephanie; Ahn, Paul Hangsan
The many obstacles to productive climate change communication necessitate new approaches. Based on science communication strategies that promote engagement rather than knowledge transfer, we assigned participants ( N = 329) to randomized chat groups that discussed similarities between group members (intimacy condition) or information about climate change (information condition). This study combined Linguistic Inquiry and Word Count (LIWC) and rhetorical analysis and found that groups in the intimacy condition were more likely to exhibit commonality than groups in the information condition. This study offers practical strategies for having productive discussions on controversial scientific topics such as climate change.